2009
DOI: 10.1182/blood-2008-11-191288
|View full text |Cite
|
Sign up to set email alerts
|

Injection of glycosylated recombinant simian IL-7 provokes rapid and massive T-cell homing in rhesus macaques

Abstract: Interleukin-7 (IL-7), the principal cytokine implicated in thymopoiesis and peripheral T-cell homeostasis, is presently under evaluation in human diseases characterized by persistent lymphopenia. Unexpectedly, before the eventual IL-7-driven T-cell expansion, all treated patients showed a profound T-cell depletion 24 hours after injection. The current study uses the rhesus macaque model to investigate the mechanisms involved in this IL-7-induced T-cell depletion. We identify a new critical function of IL-7 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 47 publications
6
64
0
Order By: Relevance
“…These points still require clarification, but it is important to note that similar data have been obtained in a recent trial with IL-7 in macaques, in which generalized migration of T cells occurred in several tissues, but not in the LNs, early after treatment with the cytokine. 24 T EM cells seem to be the preferential target of IL-15 stimulation in vivo, as demonstrated by our experiments and by other research groups. [9][10][11] Signaling through the IL-15 receptor is critical for lymphocyte stimulation, and CD122 expression on the cell surface mirrors the expansion in the peripheral blood, with the following hierarchy: NK ϳ CD8 ϩ Ͼ CD4 ϩ and T EM Ͼ T CM Ͼ ϾT N .…”
supporting
confidence: 85%
See 2 more Smart Citations
“…These points still require clarification, but it is important to note that similar data have been obtained in a recent trial with IL-7 in macaques, in which generalized migration of T cells occurred in several tissues, but not in the LNs, early after treatment with the cytokine. 24 T EM cells seem to be the preferential target of IL-15 stimulation in vivo, as demonstrated by our experiments and by other research groups. [9][10][11] Signaling through the IL-15 receptor is critical for lymphocyte stimulation, and CD122 expression on the cell surface mirrors the expansion in the peripheral blood, with the following hierarchy: NK ϳ CD8 ϩ Ͼ CD4 ϩ and T EM Ͼ T CM Ͼ ϾT N .…”
supporting
confidence: 85%
“…At day 2 after IL-15 injection, macaques experienced transient lymphopenia ( Figure 7B), which preceded T-and NK-cell expansion at day 8. This seems to be a common effect of other cytokines of the ␥-chain family, since early lymphopenia has been also described after administration of IL-7 23,24 and IL-21. 25,26 Redistribution of lymphocytes early after therapy thus indicates that stimulation by IL-15 occurs in peripheral tissues rather than in the circulation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…23,26 R-sIL-7gly, produced and provided by Cytheris SA, was injected 3 days after the previous IFN-␣ injection.…”
Section: Ifn-␣ and R-sil-7gly Treatmentsmentioning
confidence: 99%
“…6,7 This phenomenon may reflect events that occur naturally when endogenous IL-7 increases to suprahomeostatic levels in response to lymphopenia. Although data obtained in macaques have suggested that lymph nodes, parts of the intestine, and the skin may be homing sites for T cells after IL-7 injection, 10 the anatomical sites where homeostatic processes take place and the molecular mechanisms underlying the IL-7-driven homing and proliferation of T cells in peripheral tissues remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%